Improving Students' Activities and Achievement Using the Themed Worksheets Through Discovery Learning - Chandra Permana, Adhitya (KnE Social Sciences, 2023)
Preliminary studies showed the low activity of students in science learning with classical learning completeness of 22%. This study aimed to improve students’ learning activities and learning achievements through discovery learning assisted by themed worksheets. This study improved previous research related to the implementation of discovery learning to improve the learning quality. The research was designed using the classroom action research method and was carried out in three cycles, involving 32 second grade students of secondary school. Experts validated interview, observation, and questionnaire sheets, and the test items were validated statistically. This study showed that discovery learning assisted by themed worksheets improved the average student activity to 93% and the average science learning achievements to 71.61% with a classical completeness rate of 78%. Students also accepted the themed worksheets with very high satisfaction. This study did not examine the students’ character, the correlation between activity data and student learning discovery, neither did it accommodate students with special needs. These results can be a reference for teachers to improve the quality of learning, especially for schools in rural areas that have limited technological infrastructure. Keywords: class action research, discovery learning, learning achievements, students’ activities, themed worksheets